Workplace Innovation: a search for its determinants through a systematic literature review - Almeida, Leonor; Moreira, António (Business: Theory and Practice, 2022)
Workplace innovation (WPI) plays an important role at the institutional level, enabling firms to improve their competitive advantage. However, it remains an under-researched theme. The purpose of this paper is to extend current knowledge of the mechanisms that facilitate innovations in the workplace, identifying the main determinants that leverage WPI, based on a systematic literature review (SLR). An SLR has been carried out in order to determine the main determinants of WPI. The main topics are analyzed, and then the determinants derived inductively. WPI is depicted as a wide array of topics (38) that may be clustered around five different determinants that are transverse and intertwined. This research contributes by filling the gap regarding WPI. It combines five main determinants and provides important insights into possible avenues for the research of WPI.